Fine Art Symbolism of Buta Cakil and Harjuna Characters in Javanese Culture - Slamet Subiyantoro; Kristiani Kristiani; Mulyanto Mulyanto; Aniek Hindriyani; Dwi Maryono; Esterica Yunianti; Dimas Fahrudin (International Journal of Science and Applied Science: Conference Series, 2022)
Many of today's generation are unfamiliar with Purwa shadow puppets, both in terms of figures and symbolic meanings. Despite the fact that there are many noble values that can be used as a source of character education for the younger generation as future leaders of the nation. The objective of this study is to explain the implied and explicit symbolism of the art of form in the shadow puppet figures of Purwa Buta Cakil and Harjuna in in order to better comprehend Javanese culture. This study was designed using a phenomenological qualitative approach. In-depth interview techniques, content analysis, and a literature review were used to collect the data. The validity of the data was determined by using the source triangulation technique and interviewing informants. Data analysis was carried out using the flow model of analysis technique, which included cyclical stages such as data collection, reduction, data presentation, and verification. The results reveal that Buta Cakil and Harjuna are symbols of two contradictory realities that exist in the Javanese cultural value system, mirrors of complementary pairs. The paradox of good-bad, smooth-violence, victory-loss, black-and-white, brightness-darkness, etc. The fine art of the two figures is part of Javanese culture in that it instills life values taught to the community so that their lives are safe and prosperous both outwardly and inwardly.